Cash transfers and intimate partner violence: What does the evidence say? - Cash Transfer and Intimate Partner Violence Research Collaborative; London School of Hygiene and Tropical Medicine; UNICEF Office of Research-Innocenti (International Food Policy Research Institute, 2019)
Cash transfers are a popular tool to address poverty and food insecurity, but can they also reduce women’s risk of intimate partner violence?